Electronic toll collection system using RFID technology - Rahman, Kazi Jubidur; Hasan, Mustafa Mahmud; Ahmed, Nowshin; Zaman, Rawshan (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.